"I washed and fed my mother before going to school": Understanding the psychosocial well-being of children providing chronic care for adults affected by HIV/AIDS in Western Kenya - Skovdal Morten; Ogutu Vincent O (BMC, 2009)
Abstract With improved accessibility to life-prolonging antiretroviral therapy, the treatment and care requirements of people living with HIV and AIDS resembles that of more established chronic diseases. As an increasing number of people living with HIV and AIDS in Kenya have access to ART, the primary caregivers of poor resource settings, often children, face the challenge of meeting the requirements of rigid ART adherence schedules and frequent relapses. This, and the long-term duty of care, has an impact on the primary caregiver's experience of this highly stigmatised illness - an impact that is often described in relation to psychological deprivation. Reflecting the meanings attached to caregiving by 48 children in Western Kenya, articulated in writing, through photography and drawing, individual and group interviews, this paper presents three case studies of young caregiving. Although all the children involved in the study coped with their circumstances, some better than others, we found that the meanings they attach to their circumstances impact on how well they cope. Our findings suggest that only a minority of young caregivers attach either positive or negative meanings to their circumstances, whilst the majority attaches a mix of positive and negative meanings depending on the context they are referring to. Through a continuum of psychosocial coping, we conclude that to provide appropriate care for young carers, health professionals must align their understanding and responses to the psychosocial cost of chronic care, to a more nuanced and contextual understanding of children's social agency and the social and symbolic resources evident in many African communities.